Quality of life and prevalence of osteoarticular pain in patients submitted to bariatric surgery - Grans,Rute (2012)
OBJECTIVE: To analyze quality of life and observe the prevalence of musculoskeletal pain in patients submitted to bariatric surgery. METHODS: A prospective, observational and comparative study with 26 individuals aged 18 to 60 years, 25 women, which included two evaluations, one preoperative and the other approximately 42 months after surgery. The Medical Outcomes Study 36-Item Short Form Health Survey (SF-36) and the Human Body Diagram with Visual Analogue Scale were employed. RESULTS: The individual samples showed grade III obesity, with a predominance of postoperative overweight, hypertension and diabetes in 65.4% and 42.3% of the samples, with remission of hypertension in 50% and of diabetes mellitus in 38.5% (p<0.001). The SF-36 demonstrated improved quality of life, especially in aspects related to motricity; vitality and mental health showed no significant changes. Osteoarticular pain was reported and identified in various sites by the subjects; however, 87.5% of patients in the preoperative period and 88.5% in the postoperative period reported not having any physical therapy orientation, while 65.4% reported being engaged in some type of regular physical activity after surgery (p<0.001). CONCLUSION: Morbidly obese individuals have a high probability of suffering from clinical, psychic, and musculoskeletal alterations, compromising their quality of life and showing improvement after bariatric surgery; on the other hand, the psycho-emotional manifestations did not progress in the same way.